First report of a parthenogenetic Grylloidea and new genus of Neoaclini (Insecta: Orthoptera: Grylloidea: Phalangopsidae: Phalangopsinae) - Fernandes, Maria Luiza; Zacaro, Adilson Ariza; Serrão, José Eduardo (Zootaxa, 2015)
This study describes a new genus and species of Neoaclini cricket based on specimens collected in the Brazilian Atlantic forest. In addition to the morphological description, we also report karyotype. Ubiquepuella telytokous n. sp. represents the first recorded occurrence of parthenogenesis in Grylloidea. Although the exclusively parthenogenetic reproduction is rare in Orthoptera, we acknowledge this phenomenon in this species based on successful reproduction in the laboratory setting (i.e., approximately ten generations) despite the absence of males, indicating thelytokous parthenogenesis.